1680. Activity of the Novel Engineered Antimicrobial Peptide PLG0206 Against Enterobacterales isolates. (15th December 2022) - Huang, David; Sauer, John Michael; Steckbeck, Jonathan; Shinabarger, Dean; Morrissey, Ian; Hawser, Stephen
Abstract: Background: PLG0206 is an investigational, engineered cationic antimicrobial peptide designed to overcome the shortcomings of other natural AMPs, such as toxicity and limited activity. PLG0206 has recently been shown to be well tolerated and safe in a phase 1 study. This study evaluated the activity of PLG0206 and comparator antimicrobials against Enterobacterales isolates from the IHMA repository collected from various world-wide locations in 2019. Methods: Isolates tested included Citrobacter spp. (151), Enterobacter cloacae (152), Escherichia coli (300), Klebsiella pneumoniae (300), Morganella morganii (43), Proteus spp. (152), Providencia spp. (61) and Serratia marcescens (45). Minimum inhibitory concentrations (MICs) were determined by CLSI broth microdilution in cation-adjusted Mueller Hinton broth (CA-MHB), except for PLG0206 which was tested in RPMI medium due to plate-reading difficulties with CA-MHB. The susceptibility of comparators was determined using the 2022 CLSI breakpoints. MDR was defined as resistance to ≥ 3 antibacterial classes. Results: Summary MIC and susceptibility data against Citrobacter spp., E. coli, E. cloacae, and K. pneumoniae are shown in the Table. PLG0206 retained activity against MDR isolates of Citrobacter spp. (26), E. coli (92), E. cloacae (45), and K. pneumoniae (132) with MIC50/90 values of 1/2, 1/2, 1/16 and 8/16 μg/mL, respectively. PLG0206 was essentially inactive against the Morganellaceae and Yersiniaceae isolates tested with MIC50 and MIC90 values of > 32 μg/mL (data not shown). Conclusion: PLG0206 was active against isolates from the family Enterobacteriaceae, including MDR strains. The spectrum of activity of PLG0206 ranged from being most active against Citrobacter spp. and least active against K. pneumoniae . These data suggest that the novel antimicrobial peptide PLG0206 could be a potential treatment option against infections caused by Enterobacteriaceae isolates. Disclosures: David Huang, MD, PhD, Peptilogics: Employee Jonathan Steckbeck, PhD, Peptilogics: I am CEO of Peptilogics.